1998
DOI: 10.1002/(sici)1096-8628(19981002)79:4<253::aid-ajmg5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of Wiedemann-Beckwith syndrome

Abstract: Wiedemann-Beckwith syndrome (WBS) is a heterogeneous overgrowth syndrome associated with malformations and an elevated risk of developing embryonal tumors. WBS is a multigenic disorder caused by dysregulation of imprinted growth regulatory genes within the 11p15 region. Elucidation of the genetic cause of WBS will provide important insights into the molecular and epigenetic changes associated with loss of normal growth control and cancer in this syndrome. Currently available protocols for diagnostic testing, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(23 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…In a comprehensive review of >100 tumors reported in BWS, 20% were hepatoblastoma (Lapunzina 2005). Eighty-five percent of mutations causing BWS arise de novo, while 15% have family history suggesting autosomal dominant inheritance (Li et al 1997(Li et al , 1998. SGBS is also associated with increased risk for hepatoblastoma (Li et al 2001).…”
Section: Hepatoblastomamentioning
confidence: 99%
“…In a comprehensive review of >100 tumors reported in BWS, 20% were hepatoblastoma (Lapunzina 2005). Eighty-five percent of mutations causing BWS arise de novo, while 15% have family history suggesting autosomal dominant inheritance (Li et al 1997(Li et al , 1998. SGBS is also associated with increased risk for hepatoblastoma (Li et al 2001).…”
Section: Hepatoblastomamentioning
confidence: 99%
“…Among sporadic and autosomal dominant pedigrees, mutations in CDKN1C have been observed in a small number of cases. In sporadic cases, the DNA alterations involving 11p15 include trans locations or inversions, duplications, and uni parental disomy (for a detailed review, see Li et al 37 ). Hypoglycemia occurs in up to 50% of patients with BWS (reviewed by Dunne et al 10 ).…”
Section: Hyperinsulinism In Beckwith-wiedemann Syndromementioning
confidence: 99%
“…Familial tumors also occur in Beckwith-Wiedemann syndrome, associated with dysregulation of a group of growth controlling genes on 11p15.5 [77] including paternal disomy of the IGF-II gene. Rearrangement at this locus and overexpression of IGF-II has been reported in the majority of sporadic cases of carcinoma [33,78].…”
Section: Molecular Pathogenesis Of Adrenal Cortical Tumorsmentioning
confidence: 99%